Keluarga sakinah dalam Islam - Amaliya, Nabila Salma (Maliki Interdisciplinary Journal, 2023)
There are many challenges and problems that occur in household life at this time, so that many households are hit by problems that end in a messy household. For this reason, realizing a sakinah family is something that is coveted for every human being. It really feels happy to have a family that is sprinkled with feelings of mutual affection, love, respect and protection. But it turns out that creating a family like that is not an easy thing like turning the palm of the hand. But it requires hard work and support from various parties contained in it, be it from a father, mother or child. The biggest responsibility is held by a father who has the role of being the head of the family. The role of a father is very important. A father who will move where the purpose of the family is. Likewise with a mother who plays a significant role in building the character and character of her children as well as managing family finances. however, it is not uncommon for them to experience problems within the family, both families who are materially well off and families who are deprived.